Performance Analysis of Various Filtering Algorithm for Biometrics Image - Banupriya S; Karnan M; Sivakumar R (International Journal of Computer Sciences and Engineering, 2014)
Image filtering algorithms are applied on images to remove the noise that are either present in the image during capturing in to the image during transmission. These Gaussian noise, speckle noise and salt and pepper noise are occurred when captured the image. Five different image filtering algorithms are compared with three different noises types. The Peak Signal to Noise Ratio (PSNR) and Mean Square Error (MSE) are compared by filters. The median filter gives desirable results in two parameters for the three different noises.